A.N. Krylov is the founder of the floodability theory - Vasilenko, V. M. (History of science and technology, 2015)
The article deals with the scientific heritage of Academician A.N. Krylov. Krylov significanly contributed to the development of the theory of ship and floodability theory being an outstanding mathematician and mechanic, engineer-shipbuilder and inventor, a remarkable teacher and popularizer of scientific knowled. Detailed analysis of the scientific heritage of Krylov, who devoted his life to the development of the native Navy and civilian fleet. Through A. Krylov, theories of ship and its floodability gained completeness and mathematical perfection. The tables of the ship floodbility developed by A.N. Krylov are widely used in the Navy; they became mandatory, were further developed and improved, and are applied to the present.